Future as a Game, Alternative Reality of Imagination, Entertainment: Capabilities of a Projective Approach in the Study of the Consciousness of Russian Youth - Sergey I. Belov; Igor I. Kuznetsov (RUDN Journal of Political Science, 2025)
The presented research is devoted to the study of the issue of using a projective approach in the context of addressing mass culture works within the framework of studying the images of the future of young people. The methodology of the work is based on a combination of elements of comparative and structural analysis. It is concluded that one of the most promising resources for studying the image of the future in the minds of young people are video games. However, their use in research requires the use of a projective approach and a high level of nativeness. It is also desirable to use cases of story-driven video games with a non-linear algorithm for passing. It is permissible to use cases of action works, but only in the case of games with a developed description of the game universe and its key characters, covering, among other things, a description of the interests, values, aspirations and goals of the characters.